On Target? : The International Experience with Achieving Inflation Targets - Roger, Scott (IMF Working Papers; Working Paper ;, 2005)
This paper examines the international experience with full-fledged inflation targeting monetary regimes. Stylized facts are brought together from a review of the institutional elements of inflation targeting frameworks, a comparison of actual and targeted inflation outcomes, and case studies of large inflation target misses. Inflation targets are missed about 40 percent of the time and often by substantial amounts and for prolonged periods, yet no country has dropped inflation targeting. The resilience of the inflation targeting regime is attributable to the flexibility of the framework, its high standards of transparency and accountability, and the lack of realistic alternatives.